Ҭarīqah Tarjmah al-Lugah al-‘Arabiyah Ilâ al-Lugah al-Indûněsiyah Min Khilâl al-Tahlīl al-Taqâbuliy - Tandi, Wahyuddin Wahyu (Al-Tadris: Jurnal Pendidikan Bahasa Arab, 2020)
The aims of this study are: Knowing the method of translating arabic language to indonesian language and knowing the strategy of translating arabic language to indonesian language. The approach used is descriptive qualitative approach, data sources are books, journals and research results that contain translation theory and are relevant to the theme of this study, the instrument used is documentation. In analyzing the data, Miles and Huberman's theory was used, namely: collecting data, selecting relevant data, presenting data, and drawing conclusions. The results of this study are: There are many differences between arabic language and indonesian language, in the translation method there are several things that must be considered in relation to constructive studies, including: comparing the two in terms of syntax, for example in terms of suitability between subject and predicate, structural differences, comparison of shapes and types of letters and their meanings. In addition, there are several strategies for translating, including: Differences in the structure of the two require adaptation in translation, for example: active sentence is translated as passive voice and vice versa, active sentence is translated as passive voice, masdar sometimes is translated as a verb, additional letters are not translated, and kana wa akwatuha are sometimes not translated to indonesian language.